Association Between Neddylation and Immune Response - Zhu, Jiali; Chu, Feng; Zhang, Meirong; Sun, Wenhuan; Zhou, Fangfang (Frontiers in Cell and Developmental Biology, 2022)
Neddylation is a ubiquitin-like post-translational protein modification. It occurs via the activation of the neural precursor cell expressed, developmentally downregulated protein 8 (NEDD8) by three enzymes: activating enzyme, conjugating enzyme, and ligase. NEDD8 was first isolated from the mouse brain in 1992 and was initially considered important for the development and differentiation of the central nervous system. Previously, the downregulation of neddylation was associated with some human diseases, such as neurodegenerative disorders and cancers. In recent years, neddylation has also been proven to be pivotal in various processes of the human immune system, including the regulation of inflammation, bacterial infection, viral infection, and T cell function. Additionally, NEDD8 was found to act on proteins that can affect viral transcription, leading to impaired infectivity. Here, we focused on the influence of neddylation on the innate and adaptive immune responses.